Raman spectroscopy applied to identify metabolites in urine of physically active subjects - Moreira, Letícia Parada; Silveira, Landulfo; da Silva, Alexandre Galvão; Fernandes, Adriana Barrinha; Pacheco, Marcos Tadeu Tavares; Rocco, Débora Dias Ferraretto Moura (Journal of photochemistry and photobiology. B, Biology, 2017)
Raman spectroscopy is a rapid and non-destructive technique suitable for biological fluids analysis. In this work, dispersive Raman spectroscopy has been employed as a rapid and nondestructive technique to detect the metabolites in urine of physically active subjects before and after vigorous 30min pedaling or running compared to sedentary subjects. For so, urine samples from 9 subjects were obtained before and immediately after physical activities and submitted to Raman spectroscopy (830nm excitation, 250mW laser power, 20s integration time) and compared to urine from 5 sedentary subjects. The Raman spectra of urine from sedentary showed peaks related to urea, creatinine, ketone bodies, phosphate and other nitrogenous compounds. These metabolic biomarkers presented peaks with different intensities in the urine of physically active individuals after exercises compared to before, measured by the intensity of selected peaks the Raman spectra, which means different concentrations after training. These peaks presented different intensity values for each subject before physical activity, also behaving differently compared to the post-training: some subjects presented increase while others decrease the intensity. Raman spectroscopy may allow the development of a rapid and non-destructive test for metabolic evaluation of the physical training in active and trained subjects using urine samples, allowing nutrition adjustment with the sport's performance. [Display omitted] •Evaluation of urine of physically active subjects by Raman spectroscopy is proposed.•Urea, creatinine, ketone bodies, phosphate and nitrogenous compounds were detected.•The metabolic status of the individual can be evaluated through urine.